(untitled) (Research, Society and Development, 2022)
The present work evaluated the dynamics of tucumã (Astrocaryum aculeatum G. Mey.) commercialization, consumer preferences and the diversity of fruits that supply points of sale in the municipality of Itacoatiara, Amazonas, Brazil. Semi-structured questionnaires were applied to traders, where the origin of the supply of fruits, the seasonality of price and offer of tucumã and other information associated with commercialization were verified. For consumers, the questionnaires were applied virtually, where the characteristics of the most important fruits for purchase were determined. For diversity, 900 fruits were analyzed and biometric and qualitative characteristics of these fruits were evaluated. The most important source for fruit supply was the Anebá river in Silves - AM. The total amount of fruit sold was 97 tons, with an average of 5.38 t (± 6.26). The average price of bags was 145.63 (± 65.58) and for fresh fruit was 5.72 (± 1.09). Consumers have a greater preference for medium to large, undamaged, ripe, fleshy fruits. As for the pulp, it should be little fibrous and oily. As for diversity, most of it was tucumã of the red type with epicarp and mesocarp coloration, in green/yellow and orange, respectively. On average, the fruits presented length, diameter and weight of 53.99 (± 5.85) cm, 44.18 (± 4.16) cm and 57.96 (± 14.25) g, respectively. There is a seasonality in the supply and, consequently, in the price of bags. The fruits sold in Itacoatiara - AM showed variation in their biometric and qualitative characteristics.